Cheremis Musical Styles - Nettl, Bruno (Indiana University Press, 1960)
Cheremis Musical Styles serves as a guide to a specific style of folk music only just becoming known to worldwide academia as of its original publication in 1960. The original preface by Thomas A Sebeok printed in the book had the following to say in regards to its contents: "While ... Cheremis music has received sensitive and sophisticated attention, yet it has hitherto been approached in a curiously indirect way ... . Bruno Nettl's monograph ... is the first systematic and comprehensive account of Cheremis musical style (and ancillary topics) as an autonomous object of study. ... Nettl's work ... [on] the architectural relationship between these two systems-between folk poetry and folk music-remains largely uncharted."